Genetic Association of ARHGAP21 Gene Variant with Mandibular Prognathism. (April 2015) - Perillo, L.; Monsurrò, A.; Bonci, E.; Torella, A.; Mutarelli, M.; Nigro, V.
Mandibular prognathism (MP) is a recognizable phenotype associated with dentoskeletal class III malocclusion. MP is a complex genetic trait, although familial recurrence also suggests the contribution of single inherited variations. To date, the genetic causes of MP have been investigated using linkage analysis or association studies in pooled families. Here for the first time, next-generation sequencing was used to study a single family with a large number of MP-affected members and to identify MP-related candidate genes. A 6-generation kindred with MP segregating as an autosomal dominant character was recruited. To identify family members affected by MP, a standard cephalometric procedure was used. In 5 MP subjects separated by the largest number of meioses, whole-exome sequencing was performed. Five promising missense gene variants ( BMP3, ANXA2, FLNB, HOXA2, and ARHGAP21 ) associated with MP were selected and genotyped in most other family members. In this family, MP seemed to consist of 2 distinct genetic branches. Interestingly, the Gly1121Ser variant in the ARHGAP21 gene was found to be shared by all MP individuals in the larger branch of the family with nearly complete penetrance. This variant is rare in the Caucasian population (frequency 0.00034) and is predicted as damaging by all bioinformatic algorithms. ARHGAP21 protein strengthens cell-cell adhesions and may be regulated by bone morphogenetic factors, thus influencing mandibular growth. Further studies in both animal models and human patients are required to clarify the significance of this association.